تطبيق نموذج RODRIGO لإعداد كشف الدخل على أساس الأرباح الهيكلية - الثانوية: دراسة تطبيقية على البيانات المالية المنشورة لبنك البحرين الوطني 2009 - 2010 - العاني، معاوية كريم شاكر (جامعة الموصل - كلية الإدارة والاقتصاد, 2018)
يهدف هذا البحث إلى تطبيق نموذج الأرباح الهيكلية –الثانوية لــ Louis Rodrigo لإعداد كشف الدخل المصرفي لأغراض قياس الأداء المصرفي من خلال الدمج بين معلومات هذا الكشف ومعلومات التحليل المالي والمحاسبة الإدارية. إن المشكلة الأساسية التي يتعامل معها هذا البحث تتمثل في حاجة الإدارة لكشف يساعدها على اتخاذ القرارات الداخلية بصورة سليمة وخاصة فيما يتعلق بتقييم القدرة الإيرادية للمصرف وتحليل ربحيته. ويمكن حل هذه المشكلة من خلال نموذج جديد لكشف الدخل عرضه أحد الباحثين في مصرف البرازيل المركزي، وهو (Louis Rodrigo) يهدف أساسًا لتقديم معلومات للإدارة، يقوم على أساس فصل أنشطة وأعمال المصرف إلى أنشطة هيكلية، وأخرى غير هيكلية، أو ثانوية، تحت نموذج يسمى كشف الدخل على أساس الأرباح الهيكلية –الثانوية، الفرضية الأساسية للبحث هي أن كشف الدخل الجديد أكثر قدرة على توفير معلومات تخدم الإدارة في تقييم القدرة الإيرادية للمصرف من كشف الدخل التقليدي للأغراض الخارجية. لقد تم تطبيق هذا الكشف على البيانات المالية المنشورة لمصرف البحرين الوطني للعامين 2009-2010 وذلك باستخدام البيانات المتاحة على موقع المصرف دون الولوج في تفاصيل هذه البيانات، كما تم استخدام معلومات الكشف لأغراض التحليل بالنسب المالية وتطبيق نقطة التعادل وتكلفة الفرصة البديلة كأساليب في المحاسبة الإدارية. خلص البحث إلى عدة استنتاجات منها: إن هذا الكشف يوفر إفصاحًا أكبر وأكثر انسجاما مع حاجة الإدارة للمعلومات لأغراض تقييم الأداء المصرفي وتحليل ربحية المصرف وأنه يمكن استنباط مجموعة من النسب المالية الأكثر أهمية في هذا المجال.
The aim of this study is the application of the structural- secondary earnings model - for LOUIS RODRIGO to prepare the income statement of the bank. The purpose of the new income statement is measuring the banking performance through the integration of information for the financial statement analysis and management accounting. The main problem in this research is the need of management to help them for internal decision-making, particularly with regard to evaluate the power earnings of the bank and analyze profitability. This problem can solve through a new model of the income statement introduced by one of the researchers in the Central Bank of Brazil; LOUIS RODRIGO is mainly intended to provide information to management based on the separation of activities of the bank to the activities of structural and other non-structural or minor under a model called the income statement on the basis of structural - secondary profits. The basic premise of the study is that the new income statement is more able to provide information from the current income statement in evaluating the power earnings to the bank. The new statement is to apply on the financial statements published by the National Bank of Bahrain for the years 2009-2010, using data available on the website of the bank without entering into details of these data. The information of the statement is used for the purposes of analysis by financial ratios and the application of break-even point and the opportunity cost as methods of management accounting. The study concluded several conclusions, including that this statement provides disclosures bigger and more consistent with the need of management for information for the purposes of evaluating the performance of the bank and analysis profitability and that it could devise a set of financial ratios most important in this area.
Keywords: المحاسبة الإدارية -- البيانات المالية -- كشف الدخل -- الأرباح الهيكلية -- الأرباح الثانوية -- نموذج RODRIGO -- بنك البحرين الوطني